2022
DOI: 10.1111/joor.13322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head flexion posture in patients with dysphagia

Abstract: Background The chin‐down posture is often used as a compensatory manoeuvre for patients with dysphagia. This posture presumably involves flexion of the head and/or neck, but this is not clearly defined. Objective This study aimed to assess the effects of head flexion posture in a retrospective study of videofluoroscopic examination of swallowing (VF). Methods A total of 73 patients who underwent VF both with and without head flexion posture in the lateral projection were included in the analysis. The head and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…studies. 6,8,9,[20][21][22][23][24][25][26][27][28][29] Four studies were published in Korea, four studies were published in the United States of America and the rest in Japan. Included studies were published between 1993 and 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…studies. 6,8,9,[20][21][22][23][24][25][26][27][28][29] Four studies were published in Korea, four studies were published in the United States of America and the rest in Japan. Included studies were published between 1993 and 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies did not have specific figure, 8,21,23 so only five of studies were included for data analysis. 9,20,26,28,29 The pooled data revealed moderate heterogeneity among studies (I 2 = 71%,p = .009), so we used random-effects model. The results showed that swallowing in chin-down position had a significant effect on decreasing the risk of aspiration compared with neutral position, whether thin liquid or thick liquid, and this difference was statistically significant [MD = −1.35, 95% CI (−2.25, −0.44), Z = 2.92, p < .01] (see Figure 4).…”
Section: Effects On Aspirationmentioning
confidence: 99%
See 3 more Smart Citations